No College Students Left Behind Digital: Reading Comprehension in Framework of Direct Reading Thinking Activity (DRTA) - Bambang Eko Hari Cahyono; Heny Kusuma Widyaningrum; Endang Sri Maruti; Nico Irawan (IJORER : International Journal of Recent Educational Research, 2025)
Objective: Students must master reading comprehension activities because obtaining known information during learning is important. Without mastering reading comprehension, students will encounter problems between studies. On the other hand, there are still not many teachers who utilize technology products during teaching, so pedagogical and didactic aspects are neglected. Therefore, this research aims to develop Google Sites learning media through the Directed Reading Thinking Activity (DRTA) strategy so that students' reading comprehension skills on nonfiction texts can run well. Method: This research includes development research (RnD) using a sample of grade IV students totaling 50. The instrument used a media and material expert validation questionnaire and a student response questionnaire after the media was tested. Results: The results showed that developing Google Sites media with the DRTA strategy for students' reading comprehension skills was declared valid by material experts at 83% and media experts at 86%.In addition, after being tested, the development of Google Sites media received a good response from students. This means that the learning media developed is of high quality. Novelty: This research emphasizes solving students' reading comprehension problems in nonfiction texts. This is done by developing Google site media designed with the DRTA strategy and then testing students to see their reading comprehension ability.